Design and Implementation of a Computer-Based Power Management System - Omenogor, O.; Imoize, A. L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Power supply is of great importance and interrupting its supply may impact negatively on our daily activities. With the application of power management systems, the vulnerability of energy is effectively managed, thereby ensuring a smooth flow of energy requirements for domestic and industrial operations. This also reconciles efficiency, safety, economic, health and environmental conditions. Therefore, this paper presents the design, construction and implementation of a computer-based power management system for household applications. It enables the user to transfer management of supply to appliances in the house to a real time monitoring, switching and control system. This is achieved by programming an Atmega 328 microcontroller, which coordinates the overall activities of the system from a central control unit through an ESP8266 module. This wireless fidelity (Wi-Fi) module is where internally processed result is being sent to the central control unit. System design shows that the interoperability of the power management system is hinged upon a Wi-Fi as the signals are sent as packets in ASCII format from the point harnessed by the GUI software. The design was tested for performance and results show that when the power up icon is clicked on the personal computer, the bulb glows and when the power down button is clicked, the bulb goes off. Also, the measured and actual current of the transformer used in the design, justifies the efficiency of the power management system. The system design was seen to be more scalable and flexible when compared with existing home automation systems, and the hardware interface module can be handled by one server when there is Wi-Fi coverage. In conclusion, it is seen that power can be effectively managed from the personal computer, thereby reducing the overall power consumption in the facility.